A 3 year old baby with wasp stings-induced multiorgan dysfunction (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below:A 3 year old healthy female baby had been stung with a swarm of wasps on her entire body while passing a coconut tree containing wasp nest at Chakoria, Cox’s Bazar. She developed severe pain and itching at the site of stings and swelling of the body within minutes. Immediately she was seen by a local physician and was treated with the injection of hydrocortisone and  pheniramine maleate. On the following day, she gradually developed yellowish tint of the whole body (Figure 1), followed by passage of reddish scanty urine. For these reasons, she was referred to Chittagong Medical College and Hospital and was treated with injection cefotaxime, flucloxacillin,  hydrocortisone and dopamine.